(untitled) (Hershey, PA, 2007)
"This book answers the demand for a thorough resource on techniques to facilitate effective collaborative learning in virtual environments. This book provides must-have information on the role of the instructor in computer-supported collaborative learning, real-world perspectives on virtual learning group collaboration, and supporting learning group motivation"--Provided by publisher.
Keywords: Group work in education,Computer-assisted instruction,Phương pháp học theo nhóm,Làm việc nhóm trong giáo dục